Search costs and risky investment in quality - Arthur Fishman; Nadav Levy (Bar-Ilan University, Department of Economics, 2011)
One striking development associated with the explosion of e-commerce is the increased transparency of sellers' quality history. In this paper we analyze how this affects firms' incentives to invest in quality when the outcome of investment is uncertain. We identify two conflicting effects. On the one hand, reducing the consumer's cost of search for quality exacerbates the negative effects of past poor performance. This increases incentives to invest, leading to higher quality. On the other hand, the fact that a firm, despite its best efforts, may fail to live up to consumers' more demanding expectations, makes investment less attractive. This discourages investment, leading to lower quality. We show that reducing the search cost leads to higher quality if the initial level of the search cost is sufficiently high but may lead to lower quality if the initial level of the search cost is sufficiently low.
Keywords: D83; L15; 330; search; internet search; quality; risky investment; E-Business; Konsumentenverhalten; Informationskosten; Investition; Produktqualität; Entscheidung bei Unsicherheit; Theorie